Cretaceous conifers and angiosperms from the Bonarelli Level; Reassessment of Massalongo's plant fossil collections of "Monte Colle", Lessini Mountains, northern Italy. (January 2015) - Gomez, Bernard; Giusberti, Luca; Roghi, Guido; Chiari, Marco; Daviero-Gomez, Véronique; Ewin, Timothy A.M.
Abstract: The lost plant fossil and fish locality of "Monte Colle", near the village of Bolca, Verona province, northern Italy has been considered to be of Eocene age since the middle of the nineteenth century. However, upon re-examination of the plant fossils, especially the specimens of Aularthrophyton Massalongo, which closely resemble the fossil conifer Frenelopsis Schenk, led us to suspect that a Cretaceous age was more probable. Fieldwork to re-evaluate the local stratigraphy, and the identification of the radiolarians Crucella cachensis Pessagno and Patellula helios (Squinabol) within the matrix of surviving hand specimens, all definitively show that the fossil bed actually belongs to the uppermost Cenomanian Bonarelli Level. With this revised age, we properly describe the gross morphology of the surviving plant specimens and reinterpret their identifications and affinities. Frenelopsis petraepurae comb. nov., Geinitzia sp., and a single angiosperm leaf type are described and the consequences for nomenclature outlined. Comparisons with coeval Cretaceous plant taxa are also discussed. Highlights: Massalongo collected fish and plant fossils from Monte Colle, Bolca, northern Italy. Several Italian museums still house specimens from this lost fossil locality. Plants consist of Frenelopsis petraepurae, Geinitzia sp. and an angiosperm leaf. Radiolarians confirm they belong to the uppermost Cenomanian Bonarelli Level.